ENHANCE VERTICULTURAL TECHNIQUE CHAIN LIQUID SUPPLEMENTARY - Donny Ardianta; Hanifah Mutia; Devi Andriani Luta (INFOKUM, 2022)
The demand for pakcoy vegetables in urban areas is quite high, but these vegetables must be supplied from outside the city or suburban areas. The limited land available is one of the reasons why urban communities cannot produce their vegetables. Urban farming is the right solution to overcome the problem of limited land. One of the urban farming technologies that can be applied is vertical plant cultivation. The purpose of this study was to determine the response of pakcoy plants to liquid complementary fertilizer in a vertical system. The materials used were green fortune pakcoy seeds, liquid complementary fertilizer, compost, husk charcoal, and NPK fertilizer while the tools used were polybags and bamboo racks. The research variables observed were the number of leaves, leaf width, plant height, plant fresh weight, and plant dry weight. The results showed significant differences in plant height, leaf width, and several leaves seen after the plants were 21 DAP. The P4 treatment with a concentration of 2.5 cc/liter of liquid Complementary Fertilizer (PPC) and in the best plant height, leaf width, number of leaves, fresh weight, and dry weight of pakcoy plants.